Phylogeny of some Solanum species (Solanaceae) based on complete chloroplast genomes (cpDNA) and individual chloroplast genes - Filiz, Ertugrul (Research in Biotechnology, 2012)
Chloroplast DNA sequences can be used to estimate phylogenetic relationships among plant taxa. There are many chloroplast sequences have been made available in public databases and these data have been used for phlyogenetic relationship and evolutionary processes. We used three Solanum species (Solanum bulbocastanum, Solanum tuberosum and Solanum lycopersicum) and Nicotiana tabacum as outgroup. We performed phylognetic analysis four species based on complete chloroplast DNA (cpDNA), matK coding region and trnL-trnF noncoding region by using Maximum Likelihood (ML), Neighbor-joining (NJ) and unweighted pair group method with arithmetic mean (UPGMA) models. The all tree resulting from complete cpDNA clearly separated Solanum species with high bootstrap values and all the chloroplast segments clearly differentiated the genus Nicotiana tabacum from Solanum species. Tajima’s neutrality test revealed that the highest nucleotide diversity (0.01667) was observed in trnL-trnF non-coding region. UPGMA phylogenetic inference has been shown to be more robust to ML and NJ due to bootstrap values. Particularly, ML inference has lower phylogenetic resolution than UPGMA and NJ tree.